Epistemological Decolonization and Education. International Perspectives (Foro de Educacion, 2020)
It is increasingly argued that European colonialism has left its mark not only in the political and economic structures of the current world system, but also in the fields of culture, science and education. Against this background, the demand for a comprehensive epistemic or epistemological decolonization is raised. This issue follows on from this demand to clarify to what extent the phenomena of cultural colonization and coloniality also affect the fields of pedagogy and educational science. In particular, the meaning of the demand for epistemic or epistemological decolonization in the field of education will be discussed. In the introduction to this volume, the main features of decolonial thinking are presented. This is a movement of critical thinking that starts from the history of Latin America in order to reconstruct, criticize and deconstruct the globally powerful connection between modernity and coloniality. After this short introduction, the individual contributions from this issue on decoloniality will be briefly presented. Finally, the differences and similarities of the individual articles are briefly referred to. In the end, the question is raised, whether decolonial education should distinguish itself more strongly within the discipline.